Portraits of Medieval Eastern Europe, 800-1250 - Ostrowski, Donald G., author.
1 online resource (xxvi, 208 pages)
Keywords: "Portraits of Medieval Eastern Europe provides imagined biographies of twenty different figures from all walks of life living in Eastern Europe from 900 to 1400. Moving beyond the usual boundaries of speculative history, the book presents innovative and creative interpretations of the people, places, and events of medieval Eastern Europe and provides an insight into medieval life from Scandinavia to Byzantium. Each chapter explores a different figure and together they present snapshots of life across a wide range of different social backgrounds. Among the figures are both imagined and historical characters, including the Byzantine Princess Anna Porphyrogenita, a Jewish traveller, a slave, the Mongol general Sübodei, a woman from Novgorod, and a Rus' pilgrim. A range of different narrative styles are also used throughout the book, from omniscient third-person narrators to diary entries, letters, and travel accounts. By using primary sources to construct the lives of, and give a voice to, the types of people who existed within medieval European history, Portraits of Medieval Eastern Europe provides a highly accessible introduction to the period. Accompanied by a new and interactive companion website, it is the perfect teaching aid to support and excite students of medieval Eastern Europe."--Provided by publisher.